CHINESE STUDENTS IN RUSSIA - Natalia Yu. Filimonova; Elena S. Romanyuk (Высшее образование в России)
The article focuses on the conditions of formation of intercultural communications as a specific form of interaction in foreign audience by an example of the Chinese contingent. The paper aims to show the specificity of preBuniversity training of the Chinese students at Russian higher education institution and to give recommendations to teachersBexperts. While modeling of pedagogical situations it is necessary to reckon with national mentality of foreign pupils and define a number of pedagogical conditions to ensure an intercultural dialogue in a foreign audience including theoretical knowledge of teachers working with foreign audience in the field of ethnopsychology and ethnopedagogics and their psychoBpedagogical preparation. Skills and abilities of intercultural communication facilitate students’ adaptation to a new cultural environment and promote their further studying at Russian university.